Bird diversity rate as variable of land use change protection scenario using a system dynamics approach - FEBRI HANDOYO; SOEMARNO SOEMARNO; SUDARTO SUDARTO; LUCHMAN HAKIM (Society for Indonesian Biodiversity, 2024)
Abstract. Handoyo F, Soemarno, Sudarto, Hakim L. 2024. Bird diversity rate as variable of land use change protection scenario using a system dynamics approach. Biodiversitas 25: 2463-2477. The existence of enclave villages in Bromo Tengger Semeru National Park, East Java, Indonesia raises concerns about land use changes in the conservation areas. This study analyzed the position of bird diversity rate as a variable in system dynamics modeling. Data from the results of the stock flow diagram simulation, which consists of the bird diversity rate variable, along with other variables, are references used for assessing answers regarding efforts to protect conservation areas through several scenarios. The aim of this study was to predict the best scenario for the protection of national park areas that include the bird diversity rate as a variable. Bird species observations at 2 sites found 21 families and 34 species out of 135 total recorded individuals. The diversity index (H') is relatively high, the Evenness Index (E) is relatively evenly distributed between species. The Margallef Richness Index (R) at location 1 is classified as medium and location 2 is classified as low. The simulation results of stock flow diagram model (2015-2050) shows that the national park area, decreased. Measurements of bird diversity rate have also decreased. The best interventions seen in scenario 2 and scenario 3 have a good impact on reducing land use change. Protection of national park areas in scenario 3 can increase bird species diversity rate by up to 76% by implementing important actions in ecosystem improvement.